Development of Interactive Media Articulate Storyline 3 on Earth Structure Material to Improve Elementary School Students' Science Learning Outcomes - Syo’immatun Nisa’; Sigit Yulianto (Postgraduate, University of Mataram, 2025)
This study aims to develop, test the feasibility and effectiveness of interactive learning media Articulate Storyline 3 to improve learning outcomes in grade V students at SDN Sembaturagung 02 Pati Regency. This type of research is development research (R&D) using the Borg and Gall model. The subjects of this study were grade V students of SDN Sembaturagung 02 totaling 29 students in the 2024/2025 academic year. Data collection techniques used test techniques (pretest-posttest) and non-tests in the form of observation, interviews, questionnaires, and documentation. The results of this study indicate that the development of interactive media Articulate Storyline 3 is effective in improving the science learning outcomes of grade V students of SDN Sembaturagung 02 Pati Regency. This is evident from the results of the feasibility test obtained by the percentage of assessment by material experts, namely 90.20% and media experts 92.50% with the criteria